Kirkpatrick–Baez mirrors to focus hard X‐rays in two dimensions as fabricated, tested and installed at the Advanced Photon Source. (9th May 2014) - Kujala, Naresh; Marathe, Shashidhara; Shu, Deming; Shi, Bing; Qian, Jun; Maxey, Evan; Finney, Lydia; Macrander, Albert; Assoufid, Lahsen
<x xml:space="preserve">Abstract</x> The micro‐focusing performance for hard X‐rays of a fixed‐geometry elliptical Kirkpatrick–Baez (K–B) mirrors assembly fabricated, tested and finally implemented at the micro‐probe beamline 8‐BM of the Advanced Photon Source is reported. Testing of the K–B mirror system was performed at the optics and detector test beamline 1‐BM. K–B mirrors of length 80 mm and 60 mm were fabricated by profile coating with Pt metal to produce focal lengths of 250 mm and 155 mm for 3 mrad incident angle. For the critical angle of Pt, a broad bandwidth of energies up to 20 keV applies. The classical K–B sequential mirror geometry was used, and mirrors were mounted on micro‐translation stages. The beam intensity profiles were measured by differentiating the curves of intensity data measured using a wire‐scanning method. A beam size of 1.3 µm (V) and 1.2 µm (H) was measured with monochromatic X‐rays of 18 keV at 1‐BM. After installation at 8‐BM the measured focus met the design requirements. In this paper the fabrication and metrology of the K–B mirrors are reported, as well as the focusing performances of the full mirrors‐plus‐mount set‐up at both beamlines.